Novel Antimicrobial Polyethylene Composites Prepared by Metallocenic in Situ Polymerization with Tio 2-Based Nanoparticles - Rabagliati-Canessa, F; Zapata-Ramirez, P (2012)
Polyethylene (PE) composites with titanium oxide (TiO 2) nanoparticles were produced via in situ polymerization representing a novel route to obtain antimicrobial polymeric materials. The TiO 2 nanoparticles synthesized by the sol-gel method were used either as-synthesized or modified organically with hexadecyltrimethoxysilane (Mod-TiO 2). These particles were added, together with the catalytic system (formed by a metallocenic catalyst and methylaluminoxane as cocatalyst), directly to the reactor, yielding in situ PE composites with 2 and 8 wt % content of nanofiller. The catalytic polymerization activity presented a slight decrease with the incorporation of the TiO 2 and Mod-TiO 2 nanoparticles compared to polymerization without filler. Regarding the properties of the composites, crystallinity increased slightly when the different nanofillers were added, and the elastic modulus increased around 15% compared to neat PE. PE/TiO 2 nanocomposites containing 8 wt % of TiO 2 exposed to UVA irradiations presented antimicrobial activity against Escherichia coli. The PE/Mod-TiO 2 nanocomposite with 8 wt % filler killed 99.99% of E. coli, regardless of light and time irradiation. © 2012 Wiley Periodicals, Inc.
Keywords: antimicrobial and mechanical properties; metallocene catalysts; nanocomposites; polyethylene (PE); TiO2 nanoparticles